1997
DOI: 10.1021/jp961760s
|View full text |Cite
|
Sign up to set email alerts
|

Translational Relaxation of Hot O(1D) by Inelastic Collision with N2 Molecule:  Ab Initio MO and Classical Trajectory Studies

Abstract: The energy transfer process of translationally hot oxygen atom O(1D) by inelastic collision with N2 molecule, fast O(1D) + N2 → slow O(1D) + N2(v,J), has been studied by means of quasi-classical trajectory calculations on the ab initio fitted potential energy surfaces (PESs). The surface hopping procedure was included in the trajectory calculations by the Landau−Zener model in order to consider contribution from the reactive trajectories, i.e., the electronic energy transfer process O(1D) + N2 → O(3P) + N2(v,J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…[159] Although in this way hoppings due to IC and hoppings due to ISC are treated inconsistently, this approach has been used to some extent in describing collision reactions. [102][103][104][105] A further improvement is the proper inclusion of spin-orbit couplings in the equation of motion which governs the evolution of the electronic populations and hence the hopping probabilities. This allows in principle to have ISC in every time step of the simulation, not just at singlet-triplet crossings.…”
Section: Dynamics Simulations Of Intersystem Crossingmentioning
confidence: 99%
See 1 more Smart Citation
“…[159] Although in this way hoppings due to IC and hoppings due to ISC are treated inconsistently, this approach has been used to some extent in describing collision reactions. [102][103][104][105] A further improvement is the proper inclusion of spin-orbit couplings in the equation of motion which governs the evolution of the electronic populations and hence the hopping probabilities. This allows in principle to have ISC in every time step of the simulation, not just at singlet-triplet crossings.…”
Section: Dynamics Simulations Of Intersystem Crossingmentioning
confidence: 99%
“…[99] Full-dimensional dynamical studies can be performed using extensions of the trajectory surface hopping methodology. Different schemes have been employed to investigate ISC in collision reactions like O 1 C 2 H 4 , [100][101][102][103] O 1 N 2 , [104] Na 1 HCl, [105] or S 1 H 2 [106] as well as in the dynamics of O 2 on Al surfaces. [107] Trajectory surface hopping was also used to treat ISC in molecules like sulphur dioxide, [108] acrolein, [109] acetone, [110] pentanal, [111] 2-butene, [112] 6-thioguanine, [113] cytosine, [114,115] uracil, [116] as well as few transition-metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, 3 we showed that the quenching probability for the reaction O( 1 D)ϩN 2 →O( 3 P)ϩN 2 (v,J) is decreased as well as in S( 1 D)ϩCO reaction. This means that dynamics of both reactions are qualitatively similar to each other due to the fact that shape of PESs is quite analogous in both reactions.…”
Section: B Comparison With An Energy Transfer Reaction O" 1 D…؉n 2˜omentioning
confidence: 72%
“…2 In order to elucidate theoretically these characteristics, we have investigated a prototype quenching reaction O( 1 D)ϩN 2 →O( 3 P) ϩN 2 (v,J) by means of ab initio MO and the surface hopping trajectory calculations. 3 The results are summarized as follows: The singlet and triplet state potential-energy surfaces are composed of attractive and repulsive shape, respectively. There are two reaction channels leading to the products: One is a complex channel in which the reaction proceeds via complex region and the other one is a direct channel in which the reaction occurs directly without complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry optimization and energy calculation were carried out for the local minima, the transition states, and the other point on the lowest singlet and triplet PESs of CO 3 by the quadratic configuration interaction singles and doubles (QCISD) [19 -21] method with 6-311G(d) [22,23] basis sets. The harmonic vibration frequencies were calculated to characterize the stationary points as minimum or first-order saddle points, and to obtain zero-point vibration energy (ZPE) as well as force constant needed for the intrinsic reaction coordinate (IRC) calculations.…”
Section: Methodsmentioning
confidence: 99%